Slovenske književnice v Avstriji - Borovnik, Silvija (Slavistična revija, 2006)
The article surveys literary work by mainly Slovene women poets in Austria. These are on the one hand Carinthian poets Milka Hartman, Maja Haderlap, and Cvetka Lipuš, on the other Maruša Krese, who lives in Germany, but has published most of her poems in Klagenfurt, and Milena Merlak Detela, who since the 1960s lived and worked in Vienna and published in Austria. Slovene authors seem to be special characters who fail to conform to the canons of the social or literary world. Unlike their male literary colleagues, they mostly deal with topics of nation, eroticism, and the woman's position in the modern world.
Keywords: Austria; Avstrija; Celovec; Dunaj; eroticism; erotika; female writers; jezikovni artizem; Klagenfurt; linguistic artistry; narod; nation; people; pesnice; pisateljice; poetry; poezija; prose; proza; Slovene literature; slovenska književnost; slovenska Koroška; slovenska poezija; slovenska zamejska književnost; Vienna; vloga ženske; women's role